2019
DOI: 10.3390/ijms20174282
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampus Metabolic Disturbance and Autophagy Deficiency in Olfactory Bulbectomized Rats and the Modulatory Effect of Fluoxetine

Abstract: An olfactory bulbectomy (OBX) rodent is a widely-used model for depression (especially for agitated depression). The present study aims to investigate the hippocampus metabolic profile and autophagy-related pathways in OBX rats and to explore the modulatory roles of fluoxetine. OBX rats were given a 30-day fluoxetine treatment after post-surgery rehabilitation, and then behavioral changes were evaluated. Subsequently, the hippocampus was harvested for metabonomics analysis and Western blot detection. As a resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 68 publications
0
18
0
Order By: Relevance
“…Epidemiological studies and clinical trials showed that fatty acids are associated with cardiovascular diseases [ 1 , 2 , 3 , 4 , 5 ], neurological diseases [ 6 , 7 , 8 , 9 ], non-alcoholic fatty liver disease [ 10 , 11 , 12 , 13 ], allergic diseases [ 14 , 15 , 16 ], and so on. Evidence from metabolomics experiments indicates that they participate in the metabolic pathways of related diseases [ 8 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. For example, the free FA profile was found to be altered in both leukemia and pre-leukemic diseases, particularly C14:0, C16:0, and C18:0 [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies and clinical trials showed that fatty acids are associated with cardiovascular diseases [ 1 , 2 , 3 , 4 , 5 ], neurological diseases [ 6 , 7 , 8 , 9 ], non-alcoholic fatty liver disease [ 10 , 11 , 12 , 13 ], allergic diseases [ 14 , 15 , 16 ], and so on. Evidence from metabolomics experiments indicates that they participate in the metabolic pathways of related diseases [ 8 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. For example, the free FA profile was found to be altered in both leukemia and pre-leukemic diseases, particularly C14:0, C16:0, and C18:0 [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, autophagy was inhibited in the hippocampus of OBX rats (a depression animal model) and upregulated by fluoxetine (a widely used antidepressant belonging to selective serotonin reuptake inhibitors (SSRIs)) with reversal of depressive-like behavior and enhanced expression of LC3-II, Beclin1, etc. [ 13 ]. Other studies also presented decreased autophagic markers [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Olfactory dysfunction is considered a premotor sign of neurodegeneration that appears early in the degenerative process as in Alzheimer disease and Parkinson disease ( 30 , 31 ). Moreover, the olfactory bulbectomy of rats has been validated as a model of depression over the past 30 years, suggesting a close relationship between MOB and depression ( 15 17 ). Reviewing literature showed that the, pathophysiology of MOB induced by CUMS is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Although the relationship between MOB and depression was recently reported ( 15 17 ), the CUMS-induced dysfunction of MOB is not clearly described. Therefore, the current research was designed to evaluate the CUMS-induced alterations occurred in MOB in mice exposed to mild chronic depression and the efficacy of inhalation of O. basilicum essential oils in improving these changes as well as understand the possible mechanism underlying this effect.…”
Section: Introductionmentioning
confidence: 99%